Analisis Implementasi Program Paket C Setara SMA di Sanggar Kegiatan Belajar Kabupaten Karanganyar - Suwanto, Suwanto; , Prof. Dr. Sutama, M.Pd; , Dr. Sumardi, M.Si (2016)
Nonformal education was held for citizens who need educational services that serves as a substitute, an adders, and a formal education complement in order to support lifelong education. Equivalent education Package C program Equivalent Senior High School was one of non-formal education which was held to provide Senior high school level education services for citizens who do not have a senior high school diploma. The aim of the research to analyse : (1). the implementation of content standar, (2). the implementation of graduation of competition standar, (3) the implementation of process standar, (4). the implementation of teacher and administrator standar, (5) the implementation of management standar of Package C program equivalent senior high school in Sanggar Kegiatan Belajar Karanganyar regency.Using qualitative method research and using describtif qualitative analyse data with descrepancy model shows that : (1) there are discrepancies of implementation on content standar on proponent of Curriculum on Educational Items Level (CEIL) sub component in Curriculum on Educational Items Level (CEIL) document basis arranging and Curriculum on Educational Items Level (CEIL) document indicators. (2) there are discrepancies of implementation on graduation of competition standar on minimal completeness criteria on minimal completeness criteria sub component in completeness of minimal completeness criteria determining document, minimal completeness criteria each subject, and document of determining graduation criteria indicators. (3) there are discrepancies of process standar on Learning Implementation Design (LID) sub component in self learning model Learning Implementation Design (LID) indicator and sub component of learning implementation in face to face,tutorial,and self learning model,and learning contract indicators, on teaching process supervision in monitoring program, supervised by organizer, and supervised by inspector indicators, (4) there are discrepancies of implementation on teacher and administrator standar on teacher sub component in academic background, suitability of academic with subject teaching, and tutor training certificate, on administrator sub component in administrator training certificate indicators, (5) there are discrepancies of implementation on management standar on design program sub component in the middle period activity design and content of Annual Activity Design (AAD) indicator. Key words : discrepancy model,education nasional standar, equivalent education